The concentration of optimum dissolved oxygen levels for growth of mangrove crab Scylla serrata seed in recirculation system - Kurnia Faturrohman; Kukuh Nirmala; Daniel Djokosetiyanto; Yuni Puji Hastuti (Jurnal Akuakultur Indonesia)
ABSTRACT